Cangkang Kerang Sebagai Subsitusi Agregat Halus terhadap Kuat Tekan Beton - Saputra, Edo Dwi; Misdalena, Felly; Zain, Alfath (Universitas Batanghari Jambi, 2025)
Concrete is a major construction material that is often used in modern construction due to its flexibility and durability. This study aims to examine the potential of green mussel shells as a partial substitute for fine aggregate in concrete mixtures. Green mussel shells, which are mostly composed of calcium carbonate, offer an environmentally friendly solution by utilizing waste to support the sustainability of the construction industry. This study used an experimental method with variations in green mussel shell substitution of 0%, 5%, 10%, 15%, and 20%. The concrete making process involves mixing cement, coarse aggregate, fine aggregate, water, and crushed mussel shells. The concrete compressive strength test was carried out after curing for 28 days. The results showed that the higher the percentage of mussel shell substitution, the lower the compressive strength of the resulting concrete. At low substitution (5%-10%), concrete still meets the criteria for non-structural applications, with an average compressive strength ranging from 8.37 MPa to 9.05 MPa. At high substitution (15%-20%), the compressive strength of concrete decreased significantly to an average of 6.48 MPa. Substitution of green mussel shells has the potential as an alternative material in concrete, taking into account the maximum limits of its use to maintain the mechanical performance of concrete.